Mixed Mullerian tumor: a case report - Nazneen, Mahrukh; Wankhede, Uma N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Malignant mixed Müllerian tumor, also known as malignant mixed mesodermal tumor, MMMT and carcinosarcoma, is a malignant neoplasm found in the uterus, the ovaries, the fallopian tubes and other parts of the body that contains both carcinomatous (epithelial tissue) and sarcomatous (connective tissue) components. A 50-year female P1L1A1 with complaints of pervaginum bleeding and pain in abdomen was diagnosed to have carcinosarcoma endometrium for which hysterectomy with bilateral salphingo-opherectomy was done.